The sea louse Caligus elongatus (Caligidae). Genetic variation and host use by its two genotypes - Persson, Hanne Log (The University of Bergen, 2022)
Caligus elongatus (Caligidae: Siphonostomatoida) is a common ectoparasite of fish in the north Atlantic. Unlike the salmon louse (Lepeophtheirus salmonis) which is specific to salmonids, C. elongatus infects more than 80 fish species and is considered an unspecific generalist parasite. It is registered on most common fish species in Norway, including farmed fish like Atlantic salmon (Salmo salar), Atlantic cod (Gadus morhua), Atlantic halibut (Hippoglossus hippoglossus) and lumpfish (Cyclopterus lumpus). Sudden infections with high intensities of adult C. elongatus on these farmed fish have been observed, without a preceding infection with chalimus larvae. Therefore, it is likely that these adult lice originate from wild fish outside the farms. We raise the question what role small-sized fish acting as intermediate hosts could play into the infections on farmed fish. It was recently discovered that C. elongatus actually consists of two (mtDNA) genotypes, genotype 1 and 2, which may be sibling species. This discovery necessitates renewed research into the ecology of the two C. elongatus variants, since much past work could have concerned a mix of these. Some recent studies provide indications of different host use, temporal occurrence and geographical distribution of the genotypes. The aim of the present work was to examine the genetic variation, morphology and aspects of the ecology of the C. elongatus genotypes. A likely intermediate host, the two-spotted goby (Gobiusculus flavescens), was sampled throughout a year to assess the infection dynamics of C. elongatus at a locality in western-Norway. Lice from these gobies, and additional ones from various sympatric hosts and from other locations from the north-east Atlantic, were genotyped. A novel primer assay based on the cytrochrome oxidase 1 (CO1) gene was tested. The CO1 gene was sequenced from 94 lice, and compared to reference sequences in GenBank. The prevalence of C. elongatus on two-spotted gobies peaked in May (10%) and October (5%). Nearly all were ...